LAYANAN BIMBINGAN KELOMPOK TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN KEPERCAYAAN DIRI PADA SISWA DI SMA 1 BAE KUDUS - Nova Yasmine Maharani; Edris Zamroni; Arista Kiswantoro (Program Studi Bimbingan dan Konseling, 2025)
Confidence is the belief that allows individuals to have a positive outlook on themselves and their surroundings. This positive outlook enables a person to optimize their potential. Group counseling services that use cognitive restructuring techniques can provide students with a deeper understanding. This study focuses on efforts to increase the confidence of students at SMA 1 Bae Kudus. The objectives of this study are: 1. To determine the effectiveness of group counseling services with cognitive restructuring techniques in increasing confidence. 2. To assess the level of students' confidence before and after receiving group counseling services with cognitive restructuring techniques. This study is quantitative and uses a pre-test and post-test method with one group. The research subjects consisted of 8 students from class X E-11. The dependent variable in this study is confidence, while the independent variable is group counseling services with cognitive restructuring techniques. The results of the study showed that before participating in group counseling services with cognitive restructuring techniques, students had low confidence with an average score of 103.75. After receiving the services, the confidence score increased to 155.24, with an increase of 49.64%. The hypothesis test results showed a significant difference in students' confidence before and after participating in group counseling services with cognitive restructuring techniques, with a significance value of 0.000, which is below 0.05. Based on these research findings, it is concluded that group counseling services with cognitive restructuring techniques are effective in increasing students' confidence.